The Role of Prior Mathematical Knowledge and Interest in Mathematics on Mathematical Concept Understanding Ability in Senior High School Students - Robiah Adawiyah; Meiliasari Meiliasari; Tian Abdul Aziz (IKIP Siliwangi, 2022)
The role of prior mathematical knowledge and interest in mathematics as internal factors that can influence the mathematical concept understanding ability in learning mathematics in schools is important to consider. The purpose of this study was to determine the effect of prior mathematical knowledge and interest in mathematics to mathematical concept understanding ability. This study uses a quantitative research approach with data analysis techniques using multiple linear regression analysis. The participants in this study totaled 91 students who were all students of class X MA As-syafiiyah 02 Kota Bekasi for academic year 2022/2023. The results of this study were obtained: 1) Students' prior mathematical knowledge had a significant effect on students' mathematical concept understanding partially 2) Students' interest in learning mathematics had a significant effect on student’s mathematical concept understanding partially 3) prior mathematical knowledge and interest in learning mathematics simultaneously had a significant influence to the mathematical concept understanding ability. This can be interpreted that the acquisition of students' mathematical concept understanding ability can be increased by considering the factors of prior mathematical knowledge and students' interest in learning mathematics.